A proposal of environmental indicators for a sustainable tourism in the city of Zaragoza - Medrano Aranda, Sara; Lardiés Bosque, Raúl (Geographicalia, 2015)
During the last two decades, the rapid increase of tourism activities, infrastructures and services associated with this activity, have been important in the city of Zaragoza; for this, it is essential to combine such growth with environmental sustainability criteria. Based on the environmental scope of the concept of sustainable development, a system of indicators for sustainable tourism is proposed in this paper, in order to provide a management tool to facilitate the operationalization of sustainable development in Zaragoza as a tourist destination.